Investigating the use of hybrid clones of Corymbia torelliana and Corymbia citriodora for the production of renewable bioreducers - Souza, Flávia Silva de; Delatorre, Fabíola Martins; Rocha, Sofia Maria Gonçalves; Barros, Ricardo José Tauffer; Dias Júnior, Ananias Francisco (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2024)
Charcoal is of paramount importance in the steel industry, where it is used as a reductant and heat source in the combustion of iron ore and the production of pig iron. Research has been conducted to identify wood species that produce charcoal with superior physical, mechanical, and chemical characteristics compared to those currently used in the industry. This study aimed to characterize hybrid clones of Corymbia torelliana, Corymbia citriodora, and a clone of Eucalyptus urophylla at two final pyrolysis temperatures, 350°C and 550°C, to determine which is most suitable for use in the steel industry. Two hybrid clones of Corymbia torelliana and Corymbia citriodora and one clone of Eucalyptus urophylla were analyzed, with the latter serving as a comparison standard due to its prevalent use in charcoal production. The clones, seven years old and planted in Bom Despacho, Minas Gerais, Brazil, were subjected to laboratory pyrolysis at final temperatures of 350°C and 550°C, with a heating rate of 5°C.min-1. The lignin and extractive contents of the species were measured, along with the gravimetric yields of the charcoal produced. The clones were characterized for apparent density, chemical analysis, higher, lower, and useful calorific values, energy density, and scanning electron microscopy (SEM) images. The Corymbia citriodora clone, at a pyrolysis temperature of 350°C, produced the best charcoal for steelmaking, evidenced by its high fixed carbon content (65.24%), energy density (1.26 Gcal.m⁻³), and a visually observed reduction in cracks and fissures. The hybrid clone of Corymbia citriodora presents a promising alternative, offering rapid growth and qualities that are comparable or superior to species currently used in the industry.